Low cycle fatigue of hybrid woven Kenaf Fiber reinforced epoxy composite with 1% addition of Silica Aerogel / Chok., E.Y.L. and Majid., D.L.A.A. - Chok, E.Y.L.; Majid, D.L.A.A. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
This paper presented the mechanical and fatigue behavior of woven kenaf fiber reinforced epoxy composites with the composition of 16.67% kenaf and 83.33% of epoxy (1:5 weight ratio) alongside the addition of 1% of silica aerogel into the composite. There are a number of studies concentrating on natural fibers nowadays, yet their low mechanical properties when compared to other synthetic fibers had urged the addition of filler into the composite to increase the mechanical strength. Hand layup technique was used to prepare Kenaf/Epoxy (KE) and Kenaf/Epoxy/Silica Aerogel (KES) composite alongside pure epoxy (E), 100% epoxy composite. All fatigue tests were conducted at constant stress amplitude, frequency of 5 Hz, stress ratio of 0.5 and the maximum stress applied was from 90 % to 70 % of ultimate tensile strength with decrement of 5%. The results showed that the tensile properties improved as silica aerogel is added into the composite. These results showed that the tensile strength is increased by 27.3% while stiffness decreased by 78.2% when silica aerogel is added into the composite as filler. The reduction of the stiffness is associated with the brittle nature of the filler. Similar to tensile properties, the addition of silica aerogel also had resulted better fatigue life. KES composite showed more than 100% increment in number of cycles endured when compared to KE composite.